2022
DOI: 10.1186/s43170-022-00108-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management and maize variety combination effectively control Striga asiatica in southern Africa

Abstract: Maize (Zea mays L.) is an important staple food crop in sub-Saharan Africa (SSA) and contributes significantly to food security. Due to Striga, maize yield loss is estimated between 20 and 80% forcing some farmers to abandon their land therefore threatening food security. Many strategies have been applied to combat Striga infested fields to improve maize yields but alternative feasible approaches are still required. This study aimed at determining effects of phosphorus (P) and maize variety on Striga asiatica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…such as auxins and ABA are mitigated by AMF, hence, it is possible that root parasitic weeds have developed a method to intercept the communication signal and transform it into a germination-inducing signal to react when a suitable host is present (Mounde et al, 2020). This is validated by the study of Mutsvanga et al (2022) which reported higher chlorophyll contents in plants treated with AMF. Also, upon AMF inoculation, the physiological indicators including stomatal conductivity and photosynthetic rate was reportedly improved, while the biomass of Striga spp.…”
Section: Current Trends In Striga Managementmentioning
confidence: 96%
“…such as auxins and ABA are mitigated by AMF, hence, it is possible that root parasitic weeds have developed a method to intercept the communication signal and transform it into a germination-inducing signal to react when a suitable host is present (Mounde et al, 2020). This is validated by the study of Mutsvanga et al (2022) which reported higher chlorophyll contents in plants treated with AMF. Also, upon AMF inoculation, the physiological indicators including stomatal conductivity and photosynthetic rate was reportedly improved, while the biomass of Striga spp.…”
Section: Current Trends In Striga Managementmentioning
confidence: 96%
“…Interestingly, these parasitic weeds can extract nutrients and water from their host plants, resulting in compromised yield quality and quantity. Over the past few decades, significant research efforts have been dedicated to addressing this challenge [3,[5][6][7][8] and minimising crop loss. The biology and ecology of parasitic weeds are complex, as they comprise multiple interactions between the compatible host plant, the parasite, and the suitable environment [9][10][11][12] .…”
Section: Background Informationmentioning
confidence: 99%
“…Genetic tolerance and resistance have the potential to provide a long-term solution for controlling certain species of parasitic weeds [19] .  Manure application is an effective tool in controlling parasitic weeds [8,50] . Manure is a natural source of organic matter which reduces soil compaction and improves soil fertility, thus helping to suppress the growth of parasitic weeds.…”
Section: Common Control Measures Of Parasitic Weeds In Africamentioning
confidence: 99%
“…The species S. asiatica (red ower type) is predominant in Southern Africa, and S. hermonthica (purple ower) is widely distributed in Western, Central, and Eastern Africa (Dossa et al, 2023). The two holoparasites cause severe crop damage through stunting and leaf chlorosis, leading to yield losses ranging from 30-100% under severe infestation (Mutsvanga et al, 2022). Maize suffers yield losses caused by these parasites due to the paucity of Striga resistance sources in the maize gene pool, and only partial resistance has been reported.…”
Section: Introductionmentioning
confidence: 99%